ANALISIS KONSUMSI BAHAN BAKAR ALAT ANGKUT ARTICULATED DUMP TRUCK CAT D400E DITINJAU DARI PENGARUH PERAWATAN, UMUR ALAT ANGKUT PADA PENGANGKUTAN OVERBURDEN DI PT BATURONA ADIMULYA, MUSI BANYUASIN, SUMATERA SELATAN - edwin harsiga; eko indra novianto (Jurnal Teknik Patra Akademika, 2017)
Fuel consumption is an important factor that needs to be considered in conducting the activities of coal and overburden digging. High fuel consumption can be influenced by factor sharing, including: tool factor (maintenance and tool life), work field factor, and load factor. If fuel consumption increases it will cause losses for the company. Therefore, the company is required to perform maintenance on the tool so that it can make the equipment longer and also the fuel consumption can be minimized. From the results of research and calculations, tool age and maintenance can affect fuel consumption. Research has been conducted on two tools that have different tool life and also the treatment of both D400 series 1 and series 2 articulated dump truck devices. Articulated dump truck series 1 is 19 years old and series 2 is 18 years old and for articulated dump truck series 2 has been done Replacement of air filters. From this difference we can see the difference in fuel consumption of articulated dump trucks series 1 and series 2 per hour, for articulated dump truck series 1 consumes fuel: 16,588 liter / hour for 1 unit, while for articulated dump truck D400 series 2 consumes fuel: 15,741 liters / hour for 1 unit, with the difference in fuel consumption for 1 hour 1 unit of 1,053 liters.